PillarX: A Microfluidic Device to Profile Circulating Tumor Cell Clusters Based on Geometry, Deformability, and Epithelial State. Issue 17 (28th March 2022) - Green, Brenda J.; Marazzini, Margherita; Hershey, Ben; Fardin, Amir; Li, Qingsen; Wang, Zongjie; Giangreco, Giovanni; Pisati, Federica; Marchesi, Stefano; Disanza, Andrea; Frittoli, Emanuela; Martini, Emanuele; et al.
Abstract: Circulating tumor cell (CTC) clusters are associated with increased metastatic potential and worse patient prognosis, but are rare, difficult to count, and poorly characterized biophysically. The PillarX device described here is a bimodular microfluidic device (Pillar‐device and an X‐magnetic device) to profile single CTCs and clusters from whole blood based on their size, deformability, and epithelial marker expression. Larger, less deformable clusters and large single cells are captured in the Pillar‐device and sorted according to pillar gap sizes. Smaller, deformable clusters and single cells are subsequently captured in the X‐device and separated based on epithelial marker expression using functionalized magnetic nanoparticles. Clusters of established and primary breast cancer cells with variable degrees of cohesion driven by different cell‐cell adhesion protein expression are profiled in the device. Cohesive clusters exhibit a lower deformability as they travel through the pillar array, relative to less cohesive clusters, and have greater collective invasive behavior. The ability of the PillarX device to capture clusters is validated in mouse models and patients of metastatic breast cancer. Thus, this device effectively enumerates and profiles CTC clusters based on their unique geometrical, physical, and biochemical properties, and could form the basis of a novel prognostic clinical tool. Abstract : The PillarX device sorts circulating tumor cells (CTCs) and CTC clusters according to size, epithelial state and deformability. Cohesive and compact clusters are captured between pillars and demonstrate reduced deformability; while less cohesive clusters re‐arrange shape between pillars and are captured in the X‐shaped micro‐structures according to their epithelial properties. Distinct CTC cluster populations are identified from in vivo cancer models.